The many pathways of climate change affecting coastal ecosystems: a case study of western Vancouver Island, Canada - Emie Woodburn; Cathryn C. Murray; Edward J. Gregr; Kai M.A. Chan; Andy Stock (FACETS)
Climate change threatens marine ecosystems with known effects on marine life, including changes in metabolic rates, survival, and community structure. Based on a structured literature review, we developed a conceptual “pathways of effects” model that summarizes how three stressors associated with climate change (warming, acidification, and storms) affect functional species groups on the West Coast of Vancouver Island, Canada. We identified 155 distinct pathways from the three stressors through 12 categories of biological effects ranging from changes in the biochemistry of individual organisms to effects on community composition. Most species groups were affected by several climate stressors and via many pathways, although individual studies generally considered only a small fraction of relevant pathways. These effects depended on the species of interest and geographical location, highlighting the importance of local research. Climate change stressors exert complex, sometimes contradictory effects that vary across ecological scales. For example, some stressors that adversely affected a species in laboratory studies appeared beneficial in community-scale field studies. Pathways of effects models are helpful tools to summarize scientific studies across ecological scales. Compiling them in standardized databases would allow researchers and practitioners to search across species and regions to better support ecosystem-based management and environmental impact assessment.